The role of paid and unpaid labour on sorghum and finger millet production in Northern and Eastern Uganda - Gitundu, Rachel (International Crops Research Institute for the Semi-Arid Tropics, 2019)
Presented by Rachel Gitundu (International Crops Research Institute for the Semi-Arid Tropics / ICRISAT), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.